Hubungan Tingkat Konsumsi Protein dan Zat Besi dengan Kekurangan Energy Kronis (KEK) dan Anemia pada WUS Vegetarian di Pasraman Sri Sri Radha Rasesvara Badung - Muhammad Abror Faizal Maghribi; Ida Ayu Eka Padmiari; Pande Putu Sri Sugiani (Poltekkes Kemenkes Denpasar dan DPD PERSAGI Bali, 2019)
Vegetarians are a group that has a high risk of anemia and chronic energy deficiency (CED), This is because the consumption of iron and protein in the vegetarian group is considered less to meet the needs of iron and protein in the body. The purpose of the study was to determine the correlation of protein and iron consumption’s level with chronic energy deficiency and anemia in vegetarian women of childbearing age at Pasraman Sri Sri Radha Rasesvara Badung. This type of research is observational with Cross Sectional design and uses Purposive Sampling techniques, amounting to 33 people. Data were collected by interview method and measurement of upper arm circumference and hemoglobin level. Data is presented with frequency tables and cross tables then analyzed using Chi Square test. Based on the results of the analysis, there was a significant correlation between the level of protein consumption with CED in vegetarian WCA at Pasraman Sri Sri Radha Rasesvara Badung. There was no significant correlation between the level of protein consumption and anemia in vegetarian WCA at Pasraman Sri Sri Radha Rasesvara Badung. There was no significant correlation between the level of consumption of iron with CED at vegetarian WCA at Pasraman Sri Sri Radha Rasesvara Badung. There was a significant correlation between iron consumption levels and anemia in vegetarian WCA at Pasraman Sri Sri Radha Rasesvara Badung. There was a significant correlation between CED and anemia in vegetarian WCA at Pasraman Sri Sri Radha Rasesvara Badung. Keywords: Proteins and Iron Consumption’s level, CED, Anemia